Fatigue performance of welded joint between thickened-edge U-rib and deck in orthotropic steel deck. (15th February 2019) - Luo, Pengjun; Zhang, Qinghua; Bao, Yi; Bu, Yizhi
Highlights: The fatigue properties of a new rib-to-deck welded joint linking the longitudinal U-rib and deck plate of orthotropic steel deck (OSD) were investigated in this study. Seven large-scale OSD specimens, including three conventional OSDs and four OSDs utilizing the new type of rolled U-ribs, were tested under static and cyclic loadings. Fatigue tests were carried out to investigate the fatigue damage propagation process, failure mode, and fatigue resistance; and the initiation and propagation of fatigue cracks were studied in terms of the morphology. The effective notch stress method was employed to investigate the fatigue failure mechanism of the full-scale OSD specimens. Abstract: This study investigates the fatigue performance of an innovative rib-to-deck welded joint linking the longitudinal U-rib and deck plate of orthotropic steel deck (OSD). The welded joint has an increased weld depth due to the rolled U-rib with thickened edges. Seven large-scale OSD specimens, including three conventional OSDs and four OSDs with the rolled U-ribs, were tested under static and cyclic loadings. The static loading tests indicate that the welded joint may significantly change the stress distribution around the rib-to-deck joint. Fatigue tests were carried out to investigate the damage propagation process, failure mode, and fatigue resistance. The effective notch stress method is employed to evaluate the fatigue properties and failure mechanism. For both types of the OSD specimens, the predominant failure mode was cracking at the deck weld root. The fatigue resistance of the specimens that had different U-ribs were comparable, indicating that the use of the rolled U-ribs did not significantly increase the resistance to the fatigue cracking initiated at the deck weld root. This study suggests that the evaluation of fatigue resistance must be performed based on the specific failure mode.